Chrysosplenium sangzhiense (Saxifragaceae), a new species from Hunan, China - Fu, Long-Fei (PhytoKeys, 2021)
Chrysosplenium sangzhiense Hong Liu, a new species from Hunan, China, is described and illustrated. The phylogenetic analysis revealed that the new species belongs to subgen. Chrysosplenium and is closely related to C. grayanum, C. nepalense and C. sinicum. The chromosome number of the new species is 2n = 46, indicating a novel basic number x = 23 in Chrysosplenium that is different from other species. This also suggests that C. sangzhiense is probably an allopolyploid derivative of a species with x = 11 and one with x = 12. Morphologically, C. sangzhiense can be easily distinguished from C. grayanum, C. nepalense, C. sinicum and C. cavaleriei, a species not included in our phylogenetic analysis by a suite of characters relating to the sterile shoots, basal leaves, cauline leaves, flowering stem, sepals, disc, capsule and seed. A global conservation assessment is performed, and classifies C. sangzhiense as Least Concern (LC).